Respuesta :

ANSWER:  

The value of (f + g)(6) = 28

SOLUTION:

Given that f(x) = -x-2  and g(x) = [tex]x^{2}[/tex]

We need to find the value of (f+g)(6)

(f + g)(x) is an arithmetic combination of f(x) and g(x)

As, the operator between f and g is addition operator, the value of arithmetic combination becomes

(f + g)(x) = f(x) + g(x)

[tex]\begin{array}{l}{=-X-2+X^{2}} \\ {=X^{2}-X-2}\end{array}[/tex]

Now, put x = 6 in (f + g)(x)

(f + g)(6) = [tex]6^{2}[/tex]  – 6 – 2

= 36 – 6 – 2

= 36 – 8  = 28

Hence, the value of (f + g)(6) = 28